The Solid Fermentation State's Optimization of Trichoderma Harzianum M1. (October 2019) - Ming, Sui; Rong, Jiachao; Zhang, Chongjun; Li, Chunming; Zhang, Cai; Zhang, Yang; Zhou, Rongqing; Li, Guoying
Abstract: In order to exploitation a solid inoculant of Trichoderma harzianum Ml which has a significant effect on Gramineae pasture, so that it can be better in the production of the application, the solid-state fermentation substrate was optimized in this experiment. The optimal combination of the solid-state fermentation of Trichoderma harzianum Ml was screened by single factor and orthogonal experiment. The effects of carbon, nitrogen and inorganic salt on the sporulation quantity of Trichoderma harzianum M1 were further studied. The results showed that: The optimal substrate for the solid-state fermentation of Trichoderma harzianum was the ratio of grass powder: wheat bran: rice bran was 3: 2: 1, the optimal carbon source was glucose, the optimal nitrogen source was peptone, and the optimal inorganic salt was dipotassium hydrogen phosphate. Therefore, the optimal formula of Trichoderma harzianum M1 solid-state fermentation substrate was as follows: the ratio of grass powder: wheat bran: rice bran was 3: 2: 1, glucose 1%, peptone 0.05%, dipotassium hydrogen phosphate 0.01%, the number of sporulation up to 5.9×10 9 cfu/g.